2020
DOI: 10.1136/bmjsem-2020-000819
|View full text |Cite
|
Sign up to set email alerts
|

Associations between fitness, physical activity and mental health in a community sample of young British adolescents: baseline data from the Fit to Study trial

Abstract: ObjectivesTo examine relationships between fitness, physical activity and psychosocial problems among English secondary school pupils and to explore how components of physically active lifestyles are associated with mental health and well-being.MethodsA total of 7385 participants aged 11–13 took a fitness test and completed self-reported measures of physical activity, attitudes to activity, psychosocial problems and self-esteem during the Fit to Study trial. Multilevel regression, which modelled school-level c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 49 publications
2
16
0
Order By: Relevance
“…On the other hand, children and adolescents immersed in social contexts with low household income [ 1 , 36 ], low parental education [ 36 ], and poverty [ 37 ] evidence lower cognitive performance. Both physical fitness and social vulnerability seem to influence cognitive skills in children and adolescents through a broad diversity of brain health markers such as depressive symptoms, cortisol levels, neuroelectric activity, brain function, and brain macro- and microstructure [ 12 , 38 , 39 , 40 ]. Thereby, it is plausible to speculate based on the literature and our findings concerning a possible competitive process between these two environmental factors that would be more accentuated during sensitive development stages, like adolescence [ 12 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, children and adolescents immersed in social contexts with low household income [ 1 , 36 ], low parental education [ 36 ], and poverty [ 37 ] evidence lower cognitive performance. Both physical fitness and social vulnerability seem to influence cognitive skills in children and adolescents through a broad diversity of brain health markers such as depressive symptoms, cortisol levels, neuroelectric activity, brain function, and brain macro- and microstructure [ 12 , 38 , 39 , 40 ]. Thereby, it is plausible to speculate based on the literature and our findings concerning a possible competitive process between these two environmental factors that would be more accentuated during sensitive development stages, like adolescence [ 12 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results highlight the importance of exploring sex differences in research on physical activity and mental health, and that the relationship that exists is not bidirectional. Previous research in this area has demonstrated that physical activity – either measured through volume of MVPA [ 24 , 32 , 53 56 ] or sport participation [ 32 , 57 ] – has the potential to reduce the risk of depression among youth; few studies have reported results stratified by sex [ 33 , 34 ]. Aside from one study among youth that identified a bidirectional relationship between symptoms of depression and physical activity over time [ 28 ], all other analyses have investigated the bidirectional nature of this relationship among varying samples of adults [ 12 , 13 , 58 , 59 ]; only two of these identified studies examined how these relationships differ by sex [ 11 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between physical activity and mental health may have differential effects for males and females [ 26 , 33 ]. Previous research demonstrates that frequency of physical activity and fitness capabilities were both negatively correlated with internalizing disorders and psychosocial problems, however, this relationship was stronger for males than females [ 33 ]. The protective effects of physical activity on mental health may be sustained over time, although this was observed within males only [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Strengths of the study include its novelty in implementing a HIIT-style intervention at scale in a real-world setting, it being a highly scalable intervention, which was delivered at low cost [53], its broad range of secondary outcome measures (which we have already shown to be sensitive to other effects, e.g. between fitness and mental health at baseline [96]), its statistical techniques to deal with missing data, and its large cohort of young adolescents, who reported baseline PA levels that were representative of the UK [97] and the world [21], ensuring generalisability.…”
Section: Strengths and Limitationsmentioning
confidence: 99%